Application of Linear Regression to The Factors Affecting The Rice Production Level in Langsa City: Penerapan Regresi Linier Terhadap Faktor–Faktor yang Mempengaruhi Tingkat Produksi Padi di Kota Langsa - Sari, Riska Novita; Saumi, Fazrina; Olivia, Miranda; Maidita, Rizka; Salsabilah, Anastasya; Agustina, Indrianti (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
Rice is a food that produces rice which is the staple food for most of the Indonesian population. Indonesian people think that rice is a staple food that cannot be replaced, this causes the high demand for rice consumption in Indonesia. The Indonesian people, who are still very dependent on rice as a staple food, have forced the government to take steps to control the availability of rice properly. This study aims to determine the factors that influence rice production and to find out how much influence the relationship or correlation between factors has on production results. The method used in this study is multiple linear regression, this analysis is used to determine the relationship between the dependent variable and the independent variable whether each variable is positively or negatively related and see what percentage of the influence of the independent variable on the dependent variable, namely harvested area, rainfall and productivity. on rice production in Langsa City. Based on the results of the study, the results of the analysis of a strong correlation between rice production (y) and harvested area (x2) were 0.937 and results of the multiple linear test obtained a value of with a significant level of, it can be concluded that is rejected and is accepted.